Monitoring of Swelling and Degrading Behavior of Alginate Beads using Optical Tweezers - Jin, Lan; Hong, You-Chan; Pyo, Jin-Woo; Song, Hanwook; Kang, Ji Yoon; Lee, Sang Woo; Yoon, Dae Sung; Kim, Beop-Min; No, Kwangsoo (KOREAN BIOCHIP SOCIETY-KBCS, 2009)
Calcium alginate beads are widely used in drug delivery studies due to their high biocompatibility and the simple gelatinization process. It is well known that the alginate bead size changes in solutions with time, increasing initially and decreasing at a later stage. Therefore, it is essential to monitor or predict the size change of the beads since it affects the drug delivery efficiency significantly. We used the optical tweezers, a non-contact method, to investigate the temporal changes of the alginate beads in solutions instead of using the traditional drying and weighing technique. Responses to alginate concentration or external stimuli such as pH were also studied. The power spectrum method was utilized to estimate the trapping forces on the beads, which is related to the particle size changes. The results of our experiment indicate that the optical tweezers technique can continuously monitor the swelling and degrading of an alginate bead in an aqueous medium over hours which poses a high potential for drug encapsulation and release efficiency studies in the future.
Keywords: SINGLE-MOLECULE; PARTICLES; DELIVERY; CAPSULES; RELEASE; LATTICE; SYSTEM; CELLS; MODEL; TRAP